Thermoelectric transport in temperature-driven two-dimensional topological insulators - Dong, H. M. (Sci Rep, 2017)
We theoretically investigate on the thermoelectric (TE) transport properties of edge and bulk states in a temperature-driven two-dimensional (2D) topological insulator (TI) realized from CdTe/HgTe/CdTe quantum wells (QWs). It is found that the temperature can effectively drive a TI phase in CdTe/HgTe/CdTe QWs. We find that the TE transport properties of 2D TI can be governed by edge states, bulk states, or their interplay, depending on driving temperature and chemical potential of the system. Moreover, we find that the TE figure of merit ZT shows a peak at relatively low temperatures due to the competition between bulk and edge transports. This peak vanishes at relatively high temperatures due to the dominance of bulk states in the TE transport. With decreasing the ribbon width of the temperature-driven 2D TI, the low-temperature ZT exhibits two peaks, among which one occurs due to the bulk-edge competition and the other occurs due to the edge-edge hybridization; while the high-temperature ZT first exhibits the bulk-state behavior and then the edge-state one, which is indicative of a bulk-to-edge transition in the TE transport.